Pandangan Islam terhadap NFT di Era Digital - Hisny Fajrussalam; Nur Fadilah; Masruroh Masruroh; Febby Putri Marini; ya Syaikha Fatimah; Weby Khamelia (AS-SABIQUN, 2022)
In this modern era, everything has started to enter the digital realm. This can make things easier in everyday life considering the digital concept is easy access anywhere and anytime without limits. However, this can be a double-edged sword, instead of making work easier, digital concepts can be detrimental too. Therefore a policy in using and utilizing technological advances is very necessary, in order to maintain security for all users. Lately we often hear the term Non-Fungible Token or NFT for short, NFT is often associated with finance and digital economic systems that can represent a valuable item or asset. In Islam, of course, we have our own views, laws and norms in life, one of which is in economic terms. What is the Islamic view on NFT? Is NFT allowed in Islam? This research will discuss and examine these questions.